PENAFSIRAN SUFISTIK KH. SHALIH DARAT TERHADAP Q.S. AL-BAQARAH: 183 - Abshor, M. Ulil (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
Sufi interpretation is an important part in expressing the meaning contained in the Qurâ€™an, there is the meaning of outer and inner meaning. The meaning of outer is the outside of textual meaning that is the spiritual area. Sufi interpretation does not mean leaving the aspect of outer or aspects of language, but at the same time combing the inner aspect, this also happens in the book of Tafsir FaydÂ al-Rahman by KH. Shalih Darat. The intended orientation in Sufiinterpretation is more about overcoming mental problems that often forget the essence of essential life. The inner meaning will provide added value in matters of worship, especially in the interpretation of the letter (Q.S. al-Baqarah: 183). In interpreting the verse KH. Shalih Darat interprets the Isyari, so that the essential inner meaning is obtained to express the social dimensions that encourage the birth of empathy in the family, social, and among humans. So that the container in realizing superior social dimensions in the community needs to increase fasting both in terms of dhohir and in terms of the heart. The approach taken in this study uses a sufistic approach to the theory of Sufi Ishari and Isharah method (Devine Method). The results obtained from the interpretation of the verse parse about fasting there are four things, taqwa which manifests on the dimension of divinity and the human dimension of basyariah, manifests itself in the form of love between humans, disciplined life and tazqiyah al-Nafs.Keywords: Fasting, Tafsir Faidh al-Rahman, Sufistik Logic